SANKSI PIDANA DALAM MENGANTISIPASI TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA - Yuliska, Edwin (Normative Jurnal Ilmiah Hukum, 2022)
Domestic violence according to Article 1 number 1 of Law No. 23 of 2004 concerning the Elimination of Domestic Violence is any act against a person, especially a woman, that results in physical, sexual, psychological misery or suffering, and or neglect of the household. Domestic violence is commonly referred to as Hidden Crime which has many victims and this can occur in various forms and is caused by various factors. Violence against wives is a case that often occurs but is still considered normal and reasonable, especially if the violence arises only because of emotions for a moment and after that husband and wife feel remorse and forgive each other again. So far, the disclosure of victims of domestic violence (in this case the wife) is still lacking, we must be able to find cases of domestic violence every day. Disclosure of cases of domestic violence is generally faced with various problems, ranging from assuming that domestic violence is a disgrace, husband and wife because they feel love for each other or because they feel sorry for their children so that they forgive each other again, or worry if the perpetrator goes to prison. Enforcement of Law no. 23 of 2004 is expected to anticipate the level of domestic violence. In addition to the government, this can be done through seminars or counseling conducted by academics and legal practitioners from cities to remote villages in order to provide legal knowledge, especially about criminal acts of domestic violence.